2008
DOI: 10.1017/s0021859608007958
|View full text |Cite
|
Sign up to set email alerts
|

Grain quality in the Broadbalk Wheat Experiment and the winter North Atlantic Oscillation

Abstract: SUMMARYPrevious work has shown that the national average quality of the UK wheat crop from 1974 to 1999 was associated with the preceding winter North Atlantic Oscillation (NAO). The association of the winter NAO with the grain quality measure, specific weight, was shown to be mediated by sunshine duration during grain filling and unconditional wet day probability during grain ripening (the probability of a wet day following either a dry or a wet day). The present study tests the hypothesis that the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Selection of suitable parents with desirable traits and making crosses among them is an important way for increased production . Local cultivars were survived from past years until now, expected to contribute in new practices of agriculture and eff ects of climate changes which have adverse impacts on production, quality and security of human foods (Parry et al, 2004;Atkinson et al, 2008). Unless, local cultivars are not known by high grain yield, adaptability is their benefi ts for direct use by farmers or as potential plant materials in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of suitable parents with desirable traits and making crosses among them is an important way for increased production . Local cultivars were survived from past years until now, expected to contribute in new practices of agriculture and eff ects of climate changes which have adverse impacts on production, quality and security of human foods (Parry et al, 2004;Atkinson et al, 2008). Unless, local cultivars are not known by high grain yield, adaptability is their benefi ts for direct use by farmers or as potential plant materials in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Local varieties and landraces were survived from ancient years until now, expected to contribute in new practices of agriculture (sustainable or organic farming) and effects of climate changes which have adverse impacts on food production [1], food quality [2] and food security [3]. Also, the high protein content of wheat grain makes it important source of human nutrition and social economy.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated a relationship between wheat grain quality (Hagber falling number, specific weight and protein concentration) in the UK and the winter NAO (Kettlewell et al 1999;Wanner et al 2001;Hurrell et al 2003;Atkinson et al 2005Atkinson et al , 2008. According to Kettlewell et al (2003) the winter NAO has an effect on cumulative precipitation in summer in England and Wales and, consequently, on wheat quality, while Colman (1997) suggested an association between SST and NAO in the UK.…”
Section: Introductionmentioning
confidence: 99%